2010
DOI: 10.1038/onc.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

p53- and p21-dependent premature APC/C–Cdh1 activation in G2 is part of the long-term response to genotoxic stress

Abstract: The long-term cellular response to DNA damage is controlled by the tumor suppressor p53. It results in cellcycle arrest followed by DNA repair and, depending on the degree of damage inflicted, premature senescence or apoptotic cell death. Here we show that in normal diploid fibroblasts the ubiquitin ligase anaphase-promoting complex or cyclosome (APC/C)-Cdh1 becomes prematurely activated in G2 as part of the sustained long-term but not the rapid short-term response to genotoxic stress and results in the degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 58 publications
7
105
0
Order By: Relevance
“…APC is a multicomponent ubiquitin ligase well known to regulate the cell cycle. Several recent studies have indicated that APC is activated upon DNA damage in an ATM-dependent as well as an ATMindependent manner (55)(56)(57). Although it is not clear whether NF-B was involved in the DDR-induced APC activation in these studies, it is reasonable to speculate that E1-dependent activation of DDR induces activation of APC, possibly through NF-B.…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 85%
“…APC is a multicomponent ubiquitin ligase well known to regulate the cell cycle. Several recent studies have indicated that APC is activated upon DNA damage in an ATM-dependent as well as an ATMindependent manner (55)(56)(57). Although it is not clear whether NF-B was involved in the DDR-induced APC activation in these studies, it is reasonable to speculate that E1-dependent activation of DDR induces activation of APC, possibly through NF-B.…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 85%
“…This initiates the destruction of cyclin B1 and a decrease in Cdk activity, which is required to allow Cdh1-dependent activation of the APC/C during the late stages of mitosis and throughout G1. DNA damage in G2 can activate APC/C Cdh1 , which is essential for a persistent G2 arrest and requires p53-and p21-dependent Cdk inhibition (Bassermann et al, 2008;Lee et al, 2009;Sudo et al, 2001;Wiebusch and Hagemeier, 2010). Premature activation of the APC/C Cdh1 in G2 by DNA damage targets many proteins required for mitotic entry for destruction, including cyclin A, cyclin B1 and Plk1, thus preventing recovery from a G2 arrest (Fig.…”
Section: Degradation Of Cell Cycle Proteins Regulates Recovery Competmentioning
confidence: 99%
“…Premature activation of the APC/C Cdh1 in G2 by DNA damage targets many proteins required for mitotic entry for destruction, including cyclin A, cyclin B1 and Plk1, thus preventing recovery from a G2 arrest (Fig. 4A) (Johmura et al, 2014;Krenning et al, 2014;Lee et al, 2009;Lindqvist et al, 2009b;Wiebusch and Hagemeier, 2010). The resulting cells that have a G2 DNA content but lack G2-specific protein expression are committed to senescence (Johmura et al, 2014;Ye et al, 2013).…”
Section: Degradation Of Cell Cycle Proteins Regulates Recovery Competmentioning
confidence: 99%
“…2). However, subsequent work in several laboratories provided evidence that this is also due to protein degradation triggered by anaphase-promoting complex/cyclosome (APC/C) and its co-activator Cdh1 [74][75][76] (Fig. 2).…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionmentioning
confidence: 99%
“…93 Moreover, stable G2 arrest induced by ionizing radiation (IR) was associated with p53/p21-dependent premature APC/C Cdh1 activation and degradation of mitotic cyclins, consistent with previous observations. [74][75][76] However, unlike p53-mediated mitotic bypass, APC/C Cdh1 activation alone does not appear to be sufficient to induce senescence, that additionally requires repression of mitotic regulators by pRb family pocket proteins (Fig. 2).…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionmentioning
confidence: 99%